PHARMACOEPIDEMIOLOGICAL STUDY OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS AND ITS EFFECTS ON CARDIOVASCULAR SYSTEM AMONG SELECTED AREAS OF CHITRADURGA. - M., Tejaswini S.; DR, Bharathi; GR, Nataraj; Alex, Akza K; Mathew, Adarsh (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are used worldwide to treat pain and inflammation. Non-steroidal anti-inflammatory drugs (NSAIDs) are a broad class of agents with analgesic and anti-inflammatory properties that inhibit the two recognized iso enzymes of prostaglandin G/H synthase (also known as cyclo -oxygenase (COX))—namely, COX 1 and COX 2. It is generally accepted that oral non-steroidal anti-inflammatory drugs (NSAIDs) can increase the risk of acute myocardial infarction. Randomized controlled trials of NSAIDs have been of limited use for assessing this rare adverse event, as they had small cohorts and poor generalizability. The trials excluded those at highest cardiovascular risk or with established cardiovascular disease. Objectives: 1. To assess the various classes of NSAID’S giving rise to cardiovascular risks. 2. To assess the prevalence of NSAID’s induced various cardiovascular risks. Materials and Methods: The study was carried out in selected areas of Chitradurga District. Results: 1. In our study, subjects who were having CVS risks were found to be the major users of Selective cox-2 inhibitor 20(27.7) followed by preferential cox-2 inhibitor 8(11.1)) and phenyl acetic acid 6(8.3). Among 401 subjects, 72 subjects were diagnosed as cardiovascular problem. The prevalence of NSAIDs induced cardiovascular problem was found to be 18% Conclusion: Our study concluded that prevalence of cardiovascular risk due to administration of NSAIDs more in rural areas than in urban areas. Key words: NSAIDs, CVS risks, Prevalence.